2022
DOI: 10.1681/asn.2021050596
|View full text |Cite
|
Sign up to set email alerts
|

Gitelman-Like Syndrome Caused by Pathogenic Variants in mtDNA

Abstract: Background: Gitelman syndrome (GS) is the most frequent hereditary salt-losing tubulopathy characterized by hypokalemic alkalosis and hypomagnesemia. GS is caused by biallelic pathogenic variants in SLC12A3, encoding the Na+-Cl- cotransporter (NCC) expressed in the distal convoluted tubule. Pathogenic variants of CLCNKB, HNF1B, FXYD2, or KCNJ10 may result in the same renal phenotype of GS, as they can lead to reduced NCC activity. For approximately 10 percent of patients with a GS phenotype, the genotype is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 72 publications
(203 reference statements)
2
34
0
Order By: Relevance
“…Given the high energetic demand of the kidneys, the energy deficiency triggered by HNF1β defects might influence transport processes in the PT, and potentially TAL and DCT-mediated transport of Mg 2+ , Ca 2+ , and K + . Indeed, mutations in the mitochondrial DNA were recently demonstrated to cause a Gitelman-like phenotype of hypomagnesemia and hypokalemia [ 82 ].…”
Section: Mechanisms Of Disturbed Electrolyte Transport In Adtkd-hnf1β...mentioning
confidence: 99%
“…Given the high energetic demand of the kidneys, the energy deficiency triggered by HNF1β defects might influence transport processes in the PT, and potentially TAL and DCT-mediated transport of Mg 2+ , Ca 2+ , and K + . Indeed, mutations in the mitochondrial DNA were recently demonstrated to cause a Gitelman-like phenotype of hypomagnesemia and hypokalemia [ 82 ].…”
Section: Mechanisms Of Disturbed Electrolyte Transport In Adtkd-hnf1β...mentioning
confidence: 99%
“…Only recently, these findings were confirmed in 10 additional families with a maternal inheritance pattern [17 ▪▪ ]. A large European collaboration demonstrated that mitochondrial DNA variants in MT-TI and MT-TF are causative for a Gitelman-like syndrome [17 ▪▪ ]. Interestingly, the MT-TF mutations were also associated with chronic kidney disease, whereas patients with MT-TI mutations showed a preserved kidney function [17 ▪▪ ].…”
Section: Mt-ti / Mt-tf – Mitochondrial Gitelmanmentioning
confidence: 96%
“…In patient fibroblasts, the identified MT-TI and MT-TF mutations were demonstrated to reduce mitochondrial function [17 ▪▪ ]. Although the exact mechanisms remain unclear, pharmacological inhibition of complex IV, mimicking the effect of the mtDNA variants, inhibited NCC phosphorylation and NCC-mediated Na + uptake [17 ▪▪ ]. However, it should be noted that only specific MT-TI and MT-TF mutations are associated with a Gitelman-like phenotype.…”
Section: Mt-ti / Mt-tf – Mitochondrial Gitelmanmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, seven genes (namely, SCL12A1 , KCNJ1 , CLCNKA , CLCNKB , BSND , MAGED2 , SLC12A3 ) have been recognized as responsible for BS and GS, accounting for about 70–80% of genetically confirmed cases [ 1 , 5 , 14 ]. Very recently, mutations in mitochondrial DNA were reported in association with Gitelman-like phenotypes, thus expanding the genetic background of these disorders to additional patterns of inheritance [ 15 ]. In recent years, rapidly decreasing costs and turnaround time led next-generation sequencing (NGS) to spread in diagnostics of inherited tubulopathies, including BS and GS [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%